Inactivation of Different Salmonella enteriditis Phage Types and Safety and Efficacy of Inactivated Products in Chicken - A. Akhtar; M. Hair-Bejo; Elawad A. Hussein; Zunita Zakaria (Veterinary Medicine International)
This study was conducted to inactivate Salmonella enteriditis phage types (SE pt) and to determine the safety and efficacy of inactivated SE pt in chickens. SE pt 1, 3A, 6A, 7, and 35 were inactivated and inoculated (0.20 mL) in 124 chickens divided into 6 groups (CV1, CV3A, CV6A, CV7, CV35, and CV0 as a control). Sampling was conducted on day 14 after inoculation (pi). Eight chickens from each group were separated on day 14 pi for oral challenge with 0.20 mL/chicken (1010 cfu/mL) SE pt 6A and designated CV1C, CV3AC, CV6AC, CV7C, CV35C, and CV0C as control chickens. On days 7 and 14 postchallenge (pc), 4 chickens from every group were sacrificed for sampling. There was no significant difference in the body weight between different groups. In challenged groups, there was no significant association between different tissues and isolation of Salmonella on days 7 and 14 pc. There was significance (p < 0.05) in isolation of Salmonella when CV0C group was compared with other challenged groups. Significance was not observed between different tissues with respect to induction of microscopic changes. Significance was not observed between day 7 pc and day 14 pc with respect to scoring of lesions induced. Clinical signs and gross lesions were also recorded. ELISA was applied. Only in CV3AC group, the mean antibody titer was 1359 on day 14 pc. The conclusion was that inactivated SE pt 3A and 6A were safe and efficacious for protection against Salmonella enteriditis infection in chickens.